Control of radiative exciton recombination by charge transfer induced surface dipoles in MoS2 and WS2 monolayers - Hu, Peng (2018)
Due to the two dimensional confinement of electrons in a monolayer of 2D materials, the properties of monolayer can be controlled by electrical field formed on the monolayer surface. F4TCNQ was evaporated on MoS2 and WS2 monolayer forming dipoles between strong acceptor, F4TCNQ, and monolayers of MoS2 or WS2. The strong acceptor attracts electrons (charge transfer) and decreases the number of the ionized excitons. Free excitons undergo radiative recombination in both MoS2 and WS2. Moreover, the photoluminescence enhancement is stronger in WS2 where the exciton-phonon coupling is weaker. The theoretical model indicates that the surface dipole controls the radiative exciton recombination and enhances photoluminescence radiation. Deposition of F4TCNQ on the 2D monolayers enables a convenient control of the radiative exciton recombination and leads to the applications of these materials in lasers or LEDs.